PRIMER TEXTS THAT COMBINE ALPHABETIC AND ICONIC FORMS: CRITERIA FOR THEIR DESIGN - Mićić, Višnja; Vukomanović Rastegorac, Vladimir; Dragić, Želimir (Metodička teorija i praksa, 2026)
This paper focuses on primer texts that combine alphabetic and iconic representations, aiming to examine the criteria for their creation. The sample consisted of eight primers and two early readers, and the material was analysed using qualitative thematic analysis. Through this method, the following were identified: (1) four types of texts: a) unrelated sequence of sentences, b) connected sequence of sentences, c) pictorial story, and d) pictorial poem; (2) three criteria for the iconic representation of words: a) the number of letters covered, b) the presence of consonant clusters in the word, and c) the type of word. Improvements in primer texts could be directed primarily toward: (1) ensuring the presence of various text types, (2) more consistently avoiding consonant clusters in letter-based word representations, (3) the iconic representation of different word types, and (4) enhancing the aesthetic value of the text.
Keywords: methodology of teaching Serbian language and literature; early reading and writing; iconic text representation; pictorial story; pictorial poem